Local Economic Resilience: A Qualitative Study of Development Innovation in Rural Areas - Tajuddin, Imran; Mulang, Hastuti (Golden Ratio of Social Science and Education, 2024)
Amin, A., & Thrift, N. (2002). Cities: Reimagining the Urban. Wiley.Béné, C., Newsham, A., Davies, M., & Ulrichs, M. (2016). Resilience, poverty and development. Journal of International Development, 28(1), 91-111.Coleman, J. S. (1990). Foundations of Social Theory. Belknap Press.Garmendia, M., & Stagl, S. (2010). Sustainable development and innovation in rural areas. European Planning Studies, 18(2), 329-348.Harris, J., & Lewis, J. (2016). Digitalization and Rural Business Resilience: New Opportunities. Springer.Horlings, L. G., & Marsden, T. K. (2014). The New Rural Development: Sustainability and Community Innovation. Routledge.Huggins, R., & Thompson, P. (2015). Innovation, Regional Development and the Role of Government. Edward Elgar Publishing.Lemke, S., Hill, C., & Kienast, F. (2015). Global economic trends and local adaptation: A case study of rural areas. Environmental Policy and Governance, 25(6), 459-475.OECD. (2019). Rural Development and Innovation in the Global Economy. OECD Publishing.Pike, A., Rodríguez-Pose, A., & Tomaney, J. (2010). Resilience and Regional Development. Regional Studies, 44(1), 5-13.Sullivan, L., Thompson, C., & Tuan, V. (2020). Rural Innovation and Economic Resilience in Developing Economies. Routledge.Tomaney, J. (2017). Innovation in Rural Areas: Enhancing Economic Resilience. Urban Studies, 54(5), 1173-1190.